Implementation of Notary House Employment Agreements in the Selling of Land and Building - Indra Muliawan; Jawade Hafidz (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The research entitled